Clinical Aspects of Tetanus in Bali, Indonesia - mahadewa gde bagus tjokorda (Journal of Global Pharma Technology, 2017)
Tetanus is well known for its significant effects to human body. It may cause neurological deficit, systemic symptoms, and mortality in worse cases. The aim of this study was to describe comprehensive clinical aspects of tetanus in Sanglah Hospital. Tetanus prevalence in Sanglah Hospital, from June 2014 - December 2015, were 29 cases. The majority of age was less than 60 years old, predominantly were male patients. All of tetanus cases were classified as moderate-severe general tetanus. We recommended DAKAR classification in order to determine prognosis of tetanus. Most prevalent symptoms were trismus, rigidity and muscle spasm. All patients were hospitalized in isolation ward. There were tendencies to use more than one kind of antibiotics. Metronidazole and cephalosporin were the most frequently used as they were recommended by other researchers. This research showed critical period of treatment for general tetanus were on 6-7 days of admission. Mortality rate of tetanus cases in Sanglah Hospital were 27.6%. Factors that associated with mortality were incubation periods, aspiration pneumonia, sepsis, high fever and opistotonus.Keywords: Tetanus, Prevalence, Symptoms, Treatment, Mortality.